Mazání okolků kolejových vozidel ekologickými mazivy - Janovec, Ladislav (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2010)
Cílem této práce je provést rešeršní a analytické zhodnocení jednotlivých přístupů aplikovaných výrobci v oblasti mazání okolků kolejových vozidel ekologickými mazivy. Analýza je zaměřena na cyklické i kontinuální způsoby mazání jednotlivých typů centrálních mazacích systémů umisťovaných na kolejových vozidlech.

The Aim of this thesis is to search and analytical evaluation of different approaches applied by producers in the field of wheel flanges lubrication of railway vehicles by means of ecological lubricants. The analysis focuses on the cyclical and continuous methods of lubrication of different types of central lubrication systems placed on the railway vehicles.
Lubrication of flanges of railway vehicles by ecological lubricants
Keywords: tribologie; mazání kolejových vozidel; ekologická maziva; cyklické mazání; kontinuální mazání; tribology; lubrication of rolling stock; ecological lubricants; cyclic lubrication; continuous lubrication